Climate Smart Agriculture for Food Security, Adaptation, and Migration: A Review - Shambhu Katel; Honey raj Mandal; Dikshya subedi; Sagar Koirala; Sandipa Timsina; Abichal Poudel (Turkish Journal of Agriculture: Food Science and Technology)
Climate Smart Agriculture (CSA) is an integrated approach that transforms the agri-food system and mitigates climate change. They connect the use of farming techniques in order to increase food productivity, Climate resilient practice, and decrease greenhouse gases. The main aim of this review is to demonstrate the typical interrelationship between climate and agriculture and get knowledge regarding this. In addition, focus on traditional agriculture along with its mitigating measures for climate agriculture. They approach collective development practices through the efforts of individuals in order to manage agriculture and the food system under climate change. Therefore, there is an increasing need for a strategic plan to balance agriculture and the food system.